Lewis & Clark the journey of the Corps of Discovery (PBS Video, 1999)
An account of the famous "1804-1806" expedition of Lewis & Clark commissioned by President Jefferson after the U.S. purchased a vast tract of land from France in 1803 extending west from the Mississippi River to the Rocky Mountains